The solar photospheric silicon abundance according to CO5BOLD: investigating line broadening, magnetic fields, and model effects - Deshmukh, Siddhant Avinash; Ludwig, Hans-Günter; Kučinskas, A.; Steffen, M.; Barklem, P. S.; Caffau, E.; Dobrovolskas, V.; Bonifacio, P. (Astronomy and astrophysics, 2022)
Context. In this work, we present a photospheric solar silicon abundance derived using CO5BOLD model atmospheres and the LINFOR3D spectral synthesis code. Previous works have differed in their choice of a spectral line sample and model atmosphere as well as their treatment of observational material, and the solar silicon abundance has undergone a downward revision in recent years. We additionally show the effects of the chosen line sample, broadening due to velocity fields, collisional broadening, model spatial resolution, and magnetic fields. Aims. Our main aim is to derive the photospheric solar silicon abundance using updated oscillator strengths and to mitigate model shortcomings such as over-broadening of synthetic spectra. We also aim to investigate the effects of different line samples, fitting configurations, and magnetic fields on the fitted abundance and broadening values.Methods. CO5BOLD model atmospheres for the Sun were used in conjunction with the LINFOR3D spectral synthesis code to generate model spectra, which were then fit to observations in the Hamburg solar atlas. We took pixel-to-pixel signal correlations into account by means of a correlated noise model. The choice of line sample is crucial to determining abundances, and we present a sample of 11 carefully selected lines (from an initial choice of 39 lines) in both the optical and infrared, which has been made possible with newly determined oscillator strengths for the majority of these lines. Our final sample includes seven optical Si i lines, three infrared Si i lines, and one optical Si ii line. Results. We derived a photospheric solar silicon abundance of log εSi = 7.57 ± 0.04, including a −0.01 dex correction from Non-Local Thermodynamic Equilibrium (NLTE) effects. Combining this with meteoritic abundances and previously determined photospheric abundances results in a metal mass fraction Z/X = 0.0220 ± 0.0020. We found a tendency of obtaining overly broad synthetic lines. We mitigated the impact of this by devising a de-broadening procedure. The over-broadening of synthetic lines does not substantially affect the abundance determined in the end. It is primarily the line selection that affects the final fitted abundance.
Im Text ist "5" hochgestellt
Gesehen am 17.04.2023